Analysis of Quicklime and Organic Chemical Coagulant Doses in Acid Mine Water Management at PT Lematang Coal Lestari (LCL), Gunung Raja, Muara Enim, South Sumatra - Suhardiman Gumanti; Rodiyah Nursani (Jurnal Indonesia Sosial Teknologi, 2025)
Mine acid water (AAT) is one of the liquid wastes produced by coal mining activities. The existence of this liquid waste can hurt the environment, so it needs to be managed. This management aims to minimize the negative impact that will be caused. This study aims to determine the stages of AAT management and analyze the need for lime and chemical organic coagulants for coal mining at PT Lematang Coal Lestari (LCL). The method used in this study is by field observation, interview methods, and documentation as supporting data. The result of this study is that the stages of AAT management carried out by PT LCL are known, starting from AAT pumping, mixing chemical organic coagulant, measuring the pH of the inlet channel, liming the inlet channel, checking the color and pH of the outlet line water, mixing the chemical organic coagulant and liming the outlet channel if necessary, as well as settling. The lime dosage required by PT LCL is 0.32 gr/l, and the chemical organic coagulant requirement is 0.11 ml/l in one AAT water management.